THE EFFECT OF LIQUIDITY, LAVERAGE AND PROFITABILITY ON FIRM VALUE (Case Study on Sub-Sector Companies Food And Beverage Those Listed on the Indonesia Stock Exchange Period 2017-2021) - Adhista Setyarini (SEAN Institute, 2023)
This study’s aim is to analyze the effect of liquidity, leverage and profitability on firm value case studies on sub-sector companies food and beverage listed on the Indonesia Stock Exchange for the 2017-2021 period. The approach used in this study is a quantitative research approach (using data that can be measured on a numerical/numeric scale), using secondary data in the form of panel data (pooling data) that combines time series data and cross-sectional data in a period of time. In analyzing the data, researchers used a regression test with the help of an application eviews 9. The result of the study shows that liquidity has a positive and significant effect on firm value. Leverage has a positive and insignificant effect on firm value. Profitability has a positive and significant effect on firm value in sub-sector companies food and beverage listed on the Indonesia Stock Exchange for the 2017-2021 period